2002
DOI: 10.1152/ajpheart.00860.2001
|View full text |Cite
|
Sign up to set email alerts
|

QT-RR relationship in healthy subjects exhibits substantial intersubject variability and high intrasubject stability

Abstract: Recently, it was demonstrated that the QT-RR relationship pattern varies significantly among healthy individuals. We compared the intra- and interindividual variations of the QT-RR relationship. Twenty-four-hour 12-lead digital electrocardiograms (ECGs; SEER MC, GE Marquette; 10-s ECG recorded every 30 s) were obtained at baseline and after 24 h, 1 wk, and 1 mo in 75 healthy subjects (42 women, 33 men, age 27.9 +/- 9.6 vs. 26.8 +/- 7.5 yr, P = not significant). QT interval was measured automatically in each EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(143 citation statements)
references
References 35 publications
7
134
0
2
Order By: Relevance
“…Although there are considerable differences in the slope of the linear QT/RR model between subjects, there is, at least in healthy individuals, a relatively high within-subject stability. 39 In our study, the baseline slopes in LV hypertrophy were similar to what has been found in hypertrophic cardiomyopathy by Savelieva et al 12 Each individual served as his/her own control, and the changes in the QT/RR slopes were consistent with the changes in QT (and JT). The effect of irbesartan was thus towards a normalization of the relation between repolarization and the RR interval (or heart rate), while the opposite was observed when atenolol was given to patients with eccentric LV hypertrophy (see Figure 3).…”
Section: Reverse-use Dependence: Qt/rr Slopesupporting
confidence: 87%
“…Although there are considerable differences in the slope of the linear QT/RR model between subjects, there is, at least in healthy individuals, a relatively high within-subject stability. 39 In our study, the baseline slopes in LV hypertrophy were similar to what has been found in hypertrophic cardiomyopathy by Savelieva et al 12 Each individual served as his/her own control, and the changes in the QT/RR slopes were consistent with the changes in QT (and JT). The effect of irbesartan was thus towards a normalization of the relation between repolarization and the RR interval (or heart rate), while the opposite was observed when atenolol was given to patients with eccentric LV hypertrophy (see Figure 3).…”
Section: Reverse-use Dependence: Qt/rr Slopesupporting
confidence: 87%
“…On the other hand, the slope of linear regression for each animal by Fridericia's formula was significantly gentler than that by Bazett's formula, and no significant difference from that by individual correction was seen. The individual correction, a method to correct QT interval by determining a correction coefficient for each animal, has recently been regarded as important for accurate evaluation of QTc-interval changes in humans (24,25). The correction coefficient for QT interval, which was determined for each animal, in the individual correction method was similar to that in Fridericia's formula (coefficient β = 0.33).…”
Section: Discussionmentioning
confidence: 99%
“…These pairs of recordings were separated by 25 days. (That is, in each subject, 4 recordings were obtained on days 1,3,26, and 28.) Study subjects were not permitted to sleep while the Holter recordings were obtained, and extra care was taken to ensure the adherence to this requirement.…”
Section: Methodsmentioning
confidence: 99%
“…The intracellular mechanism underlying the repolarization dependency and thus the pattern of the QT/RR relationship are not completely understood and have been subject of both animal and modeling experiments of ionic currents (11,19,22). Why the QT/RR relationship and adaptation exhibits substantial intersubject differences with intrasubject stability (3,27) is not known. Further studies of the phenomenon require appropriate tools for the description of the relationship.…”
mentioning
confidence: 99%